Effects of age, gender, and risk-factors for heart failure on native myocardial T1 and extracellular volume fraction using the SASHA sequence at 1.5T - Pagano, Joseph J.; Chow, Kelvin; Paterson, D. Ian; Mikami, Yoko; Schmidt, Anna; Howarth, Andrew; White, James; Friedrich, Matthias; Oudit, Gavin Y.; Ezekowitz, Justin; Dyck, Jason; Thompson, Richard B. (Journal of magnetic resonance imaging, 2018)
Background Understanding cardiac MR T1 mapping values might require examination of the effects of age, gender, and heart failure risk factors. Purpose/Hypothesis To evaluate the effects of gender, age, and presence of heart failure risk factors on myocardial native T1 and extracellular volume fraction (ECV). Study Type Retrospective, cross-sectional, observational study. Population Secondary analysis of cardiac MR data, separated by gender and health status, based on the presence of at least one heart failure risk factor. Field Strength/Sequence Cardiac MR imaging at 1.5T, including T1 mapping using the SAturation recovery single-SHot Acquisition (SASHA) sequence. Assessment Interventricular septal region-of-interest analysis for assessment of native T1 and ECV. Statistical Tests Group comparisons performed using Student t-test, or nonparametric equivalent. Linear regression was used to assess relationships between age and T1 measurements. Results Native T1 and ECV were available in 187 and 143 subjects, respectively. T1 and ECV were independent of age in all groups (Native T1: healthy women P = 0.655; healthy men P = 0.906; at-risk women P = 0.487; at-risk men P = 0.683; ECV: healthy women P = 0.685; healthy men P = 0.199; at-risk women P = 0.152; at-risk men P = 0.747). T1 and ECV were higher in healthy women versus men (1202 ± 30 ms versus 1167 ± 36 ms, P = 0.0000 and 22 ± 2% versus 20 ± 2%, P = 0.0089), while values were similar in women and men with risk factors (1197 ± 55 ms versus 1193 ± 45 ms, P = 0.6556, 21 ± 2% versus 21 ± 3%, P = 0.5039). No differences existed in native T1 or ECV between women with or without risk factors (P = 0.6344 and P = 0.1026), whereas men with risk factors showed higher native T1 values (P = 0.0070). Data Conclusion Native T1 and ECV measured with SASHA do not vary with age, regardless of gender or the presence of factors for heart failure. Native T1 and ECV are higher in healthy women than men, but do not differ in the presence of risk factors, suggesting a different myocardial response to risk factors between genders. Level of Evidence: 3 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:1307-1317.
Gesehen am 06.03.2020